Employee Performance: Training, Coaching and Employee Engagement - Unwanullah Unwanullah (Dinasti International Journal of Education Management And Social Science, 2023)
Employee Performance: Training, Coaching and Employee Engagement is an article of scientific literature study within the subject of human resource management science. The objective of this article is to build a hypothesis of the role between variables that will be used in future research. The object of research is online libraries, Google Scholar, Mendeley and other academic online media. The method is a research library method, from e-book and open access e-journal. The results of this article are: 1) Training affects Employee Performance; 2) Coaching affects Employee Performance; and 3) Employee Engagement affects Employee Performance.